THE IMPLEMENTATION OF MITIGATION POLICY OF SIDOARJO MUDFLOW - Suwondo Putro, Prasojo Bayu (FIA UB, 2013)
Abstract: The Implementation of Mitigation Policy of Sidoarjo Mudflow. On May 29, 2006, a large-scale mudflow eruption was caused by a technical error during an oil exploration in the Sidoarjo District of the East Java province of Indonesia. The mudflow spread widely, encompassing 12 villages and forcing around 40,000 people to relocate. The mudflow is still spreading, and will continue to do so for the next 30 years. We must learn more from the mitigation policy that were implemented in order to design better policy models for future actions. This paper presents the policy implementation analysis on the mudflow disaster mitigation. We using qualitative research methods, and applying Edward III model as the analyzing tool of implementation process. The research finding is the Indonesian Government should carry out policy formulation in the form of